Active Thermoregulation in Lasius Fuliginosus Nests in Spring (Hymenoptera: Formicidae) - Stukalyuk, Stanislav; Radchenko, Yury M.; Balabukh, Vira (Sapienza University of Rome, Rome, Italy, 2025)
ENG: The aim of the study was to investigate characteristics of temperature conditions in Lasius fuliginosus nests in spring to possibly prove the spring warmup hypothesis. In spring (05.03 to 31.05.2024), 3 loggers, allowing measurements of temperature conditions were mounted on the outer walls of 3 L. fuliginosus nests in a deciduous forest near Kyiv (Ukraine). The temperature measurements were taken at 15-minute intervals. Simultaneously, the atmospheric air temperature was measured during the same period (at 3-hour intervals). Nests 1 and 2 were typical for this species: both in empty cores of oak trees (1 m diameter), while Nest 3 was auxiliary and located under a 0.05 m layer of oak bark. The physical data (air and nest wall temperatures) were used to construct a mathematical model of the thermal processes occurring in the core of a carton nest. The modelling showed that the anthills’ ability to maintain nest temperature in spring depends on their size and location inside the tree trunks exposed to environmental influence. The temperature inside a nest follows the average daily air temperature with a slight delay due to thermal inertia of the tree. The nest in tree #1 proved to be the most stable: even during cold spells as low as -5°C, the temperature in the core remained +25°C thanks to metabolic heat. Nest #2 also maintains the required temperature (+25°C) during temperature falls to +5°C. However, nest #3 does not provide conditions for offspring development during sudden cold snaps: the heat emitted is insufficient to compensate for losses at air temperatures below +20°C. This nest is not designed for active thermoregulation. It has been shown that L. fuliginosus are able to actively warm up their nest in spring, and the warmup rates (up to 25–26°C) are similar to the temperature conditions in the red forest ants’ anthills (Formica rufa group).
S. Stukalyuk: ORCID 0000-0002-9775-0750; Yu. Radchenko: ORCID 0000-0002-5055-6707; V. Balabukh: ORCID 0000-0003-3223-7531
Keywords: active thermoregulation; Lasius fuliginosus; carton nests; mathematical model; КЕТтаОП; NATURAL SCIENCES; NATURAL SCIENCES::Biology